Dual learning path: supervised internship in production engineering - Rocha, Estevão Lima de Carvalho; Oliveira, Cesar Bündchen Záccaro de (Brazilian Journal of Production Engineering, 2024)
The Production Engineering professional plays a key role in operational excellence in the industrial, commercial and service sectors. Practical professional training, through supervised internships, is essential for the development of professional skills. The aim of the research was to assess the influence of the supervised internship on the professional competencies consistent with the practice of the profession. The method employed a qualitative approach using focus group methodology. A semi-structured interview was conducted with eight undergraduates from a Production Engineering degree course in the State of Ceará. The interview revealed some of the technical and behavioral skills required by the job market. It was also found that despite welcoming production engineering students for supervised internships, some of the supervisors were unaware of the professional activities involved in their training. The results showed that poorly applied internship plans can compromise the student’s intended training. The conclusion is that the supervised internship is crucial for integrating academic theory with professional practice in Production Engineering. However, there is a need to adapt the structure of the Internship Plan to better align the planned activities with market demands.